MST 567 – Categorical Data Analysis - PPSM, Pusat Pengajian Sains Matematik (2022)
First Semester Examination 2021/2022 Academic Session FEBRUARY 2022 MST 567 – Categorical Data Analysis Duration : 3 hours 45 minutes